The Effect of Super Coach Change Projects on the Quality of Education and Training at the Center for the Development of Quality Assurance in Vocational Education in the Fields of Business and Tourism : A Narrative-Systematic Literature Review: Pengaruh Proyek Perubahan Super Coach terhadap Kualitas Pendidikan dan Pelatihan di Pusat Pengembangan Penjaminan Mutu Pendidikan Vokasi Bidang Bisnis dan Pariwisata : Tinjauan Pustaka Naratif-Sistematis - Ham Idris Tumenggung Sis; Hapzi Ali (OGZ Research & Publishing, 2026)
The change project is a core instrument in the leadership training of the State Civil Apparatus (ASN) which requires participants to design and implement real innovations in their work units. The success of a change project is largely determined by the quality of coaching mentoring, and in its development a number of educational institutions have developed a layered mentoring model known as